Pelatihan Penggunaan Software Avogadro untuk Pemodelan Senyawa Hidrokarbon Sederhana kepada Siswa Kelas XI IPA SMA Negeri 5 Maluku Tengah - Mirella Fonda Maahury; Mario Rowan Sohilait; Semuel Simra Pada (Jurnal Gema Ngabdi, 2021)
Learning Hydrocarbon at the High School requires qualified teaching aids. The limitations of teaching aids make students' knowledge of the spatial structure (3 dimensions) of hydrocarbon compounds not following the content being studied so that they do not achieve the expected competence. In the end, this impacts the difficulty of understanding the same material at a higher level, high school. For this reason, the training on the use of the Avogadro software is expected to provide knowledge to students on how to operate the software, and students can do modeling for simple hydrocarbon compounds. In the end, the students understand how the three-dimensional structure of hydrocarbon compounds looks. We need the help of software that students can use in studying molecular structures, especially hydrocarbon compounds. In this service process, a training method is carried out using demonstrations of the operating steps of the Avogadro software and is followed by all training participants. The results obtained are that the participants (Science class students of SMA Negeri 5 Maluku Tengah) can perform modeling with Avogadro software, drawing 3-dimensional structures, optimizing geometry and determining structural parameters of simple hydrocarbon molecules.